Earltonella fredricksi n. gen n. sp. and Thalassocystis striata (Chlorophyta, Bryopsidales) from the Silurian (Llandoverian) of the Timiskaming outlier, Ontario, Canada. (March 2023) - LoDuca, Steven T.; Meacher, Mike; Pepper, Mark; Brett, Kevin; Isotalo, Phillip A.
Abstract: Specimens of macroalgae are reported and described herein from newly discovered algal-Lagerstätten within the Llandoverian Earlton Formation at two localities separated by a distance of 45 km in the Timiskaming outlier of Ontario, Canada. Both localities are characterized by abundant specimens of the Codium -like bryopsidalean green alga Thalassocystis striata, the details of which, including within-assemblage morphological variation, compare closely to material from the type locality. Previously, this noncalcified taxon was known only from the Llandoverian Schoolcraft Formation in northern Michigan, ~500 km to the west. These new occurrences provide additional evidence that the alga-bearing intervals within the Earlton Formation at both Timiskaming localities correlate with the Schoolcraft Formation in the Michigan Basin. An associated noncalcified form at one of the Timiskaming localities is described as a new genus and species, Earltonella fredricksi LoDuca, n. gen. n. sp., the thallus architecture of which, with a creeping, runner-like stolon and numerous pinnate fronds, broadly resembles that of the living bryopsidalean alga Caulerpa . In broader terms, these new algal-Lagerstätten indicate that for a brief time during the late Llandoverian, as with other times during the Silurian, unusual conditions conducive to both the proliferation and preservation of expansive 'seaweed meadows' were established across regional-scale areas of the Laurentian epeiric sea.